História nas histórias: sequências didáticas para o ensino de história da antiguidade - Menger, Amanda da Silva (My University, 2025)
This paper, “History in stories: teaching sequences for teaching Ancient History,” presents the use of literature combined with history based on the production of educational materials for teaching sixth-grade elementary school classes on the subject of Ancient Greece. The proposal consists of the production of two learning sequences on the teaching of Ancient History (Greece) and includes the use of a contemporary literary text, Diário de Pilar na Grécia (Pilar's Diary in Greece), by Brazilian author Flávia Lins e Silva (2019A), with illustrations by Joana Penna. The work is intended for history teachers in the final years of elementary school. The methodology used for working with literary texts in the classroom is Literary Literacy by Rildo Cosson (2020A). The research includes theoretical discussions on the relationship between history and literature based on Chartier (2002), Pesavento (2004), and Albuquerque Júnior (2005, 2008, and 2019); as well as on the teaching of Ancient History based on the works of Funari (2004, 2016, and 2020), Guarinello (2003 and 2021), and Moerbeck (2021); and also on the reading and interpretation of written and visual texts from the chosen work, based on the theoretical basis of Santaella, Nóbrega e Prado (2012), Ramos (2018), Mendes (2019), Leite (1997), Lajolo (2018), Gancho (2014), Joly (2007) e Eagleton (2019). The teaching sequences were, in turn, constructed based on bibliography on Ancient History and Greece contained in Funari (2018), Guarinello (2019), Aleixo and Fernandes (2023), MacDonald (2019), and Matyszak (2023), supported by the methodological organization of Historical-Critical Pedagogy, in which dialectics becomes a teaching method according to Saviani (1996, 2008) and Gasparin (2009). The teaching material produced was used with the 6th grade classes of the Senador Salgado Filho Municipal Elementary School, in Gramado/RS, in the years 2022, 2023, and 2024. The case report presents the procedures for applying the teaching sequences in those years, as well as the evaluation of the students after participating in the research project. This study aims to how that it is possible to develop teaching sequences in which literature is understood as a historical source and pedagogical resource for teaching history, especially ancient history, to elementary school students, contributing to their understanding of history and the cultural legacies of Greece today. [resumo fornecido pelo autor]
O presente trabalho, História nas histórias: sequências didáticas para o ensino de História da Antiguidade, apresenta o uso da Literatura em conjunto com a História na produção de materiais didáticos sobre Grécia Antiga para o trabalho docente com turmas de 6º ano do Ensino Fundamental. A proposta consiste na produção de duas sequências didáticas sobre o ensino de História Antiga (Grécia), contemplando um texto literário contemporâneo, Diário de Pilar na Grécia, da autora brasileira Flávia Lins e Silva (2019e), com ilustrações de Joana Penna. O trabalho tem como público-alvo interessado professores de História dos anos finais do Ensino Fundamental. A metodologia utilizada para o trabalho com os textos literários em sala de aula é o Letramento Literário, de Rildo Cosson (2020a). A pesquisa conta com discussões teóricas sobre as relações entre História e Literatura a partir de Chartier (2002), Pesavento (2004) e Albuquerque Júnior (2005; 2008; 2019a; 2019b), bem como sobre o ensino de História Antiga a partir dos trabalhos de Funari (2004; 2016; 2020), Guarinello (2003; 2021) e Moerbeck (2021). Ainda, para a leitura e interpretação dos textos escritos e imagéticos da obra escolhida, conta com orientações teóricas de autores como Santaella, Nóbrega e Prado (2012), Ramos (2018), Mendes (2019), Leite (1997), Lajolo (2018), Gancho (2014), Joly (2007) e Eagleton (2019). As sequências didáticas, por sua vez, foram construídas a partir de bibliografia sobre História Antiga e Grécia, contida em Funari (2018), Guarinello (2019), Aleixo e Fernandes (2023), MacDonald (2019) e Matyszak (2023), com fundamentação na organização metodológica da Pedagogia Histórico-Crítica, na qual, conforme Saviani (1996; 2008) e Gasparin (2009), a dialética se torna um método de ensino. O material didático produzido foi trabalhado com as turmas de 6º ano da Escola Municipal de Ensino Fundamental Senador Salgado Filho, em Gramado/RS, nos anos de 2022, 2023 e 2024. No relato de caso, são apresentados os procedimentos de aplicação das sequências didáticas nos referidos anos, bem como a avaliação dos alunos após a participação no projeto de pesquisa. A proposta deste trabalho mostra que é possível o desenvolvimento de sequências didáticas em que a Literatura seja entendida como fonte histórica e como recurso pedagógica para o ensino de História - em especial, da História da Antiguidade, - junto a turmas do Ensino Fundamental, contribuindo para a compreensão da História e dos legados culturais da Grécia na atualidade. [resumo fornecido pelo autor]
Keywords: História - Estudo e ensino; História antiga; Letramento; Historiografia; Literatura e história; Prática de ensino; History - Study and teaching; History, Ancient; Literacy; Historiography; Literature and history; Student teaching